The medical treatment of patients with Parkinson's disease receiving subthalamic neurostimulation. Issue 6 (June 2015) - Alexoudi, Athanasia; Shalash, Ali; Knudsen, Karina; Witt, Karsten; Mehdorn, Maximilian; Volkmann, Jens; Deuschl, Günther
Abstract: Introduction: Deep brain stimulation of subthalamic nucleus (STN-DBS) for Parkinson's disease allows for a reduction in medication dosage. Changes in total levodopa equivalent daily dose (LEDD) have been frequently reported, there is little information about changes within the drug classes. Methods: We retrospectively assessed the changes in antiparkinsonian drugs dosages in 150 patients from one center who had preoperative and postoperative evaluations at 6 months and 3 years. Two long term subgroups with postoperative follow-up till the 5th–6th year ( n = 58) and 10th year ( n = 15) were included. Results: The major modifications in medication dosage occurred during the initial postoperative period. LEDD was reduced by 53.4% compared to baseline at 6 months and 47.9% at 3 years. Fifty six percent and 41.3% of the patients were on monotherapy, 9.3% on no medication at 6 months and 6.7% at 3 years post surgery. Patients on levodopa, or dopamine agonists showed similar reductions. At the 3rd year the oldest group of patients showed a significant decrease in dopamine agonists. The number of patients treated with amantadine was significantly reduced; however the number of patients treated with antidepressants was significantly increased over the first 3 years. Annual medication costs per patient were decreased after the DBS-STN implantation by 61.3% at 6 months and 55.4% at 3 years. Conclusion: STN-DBS allows for a reduction in the dosage of medication and the costs are similarly reduced. In this cohort different medication groups were reduced to a similar extent. Patients' demographic factors did not play a major role in the selection of treatment.